Rivers as natural capital assets: a quick scoping review to assess the evidence linking river asset condition to changes in the flow of ecosystem services - Zini, Valentina; Johnson, Natalie; Crouch, Alice; Lenagan, Gerard; Cooper, Chris; Naura, Marc; Speck, Imogen; Rouquette, Jim (Wiley, 2025)
River managers are beginning to adopt natural capital approaches in practice. However, while it is crucial for river management, the link between river asset condition and the flow of ecosystem services is poorly understood. In this study, we conducted a Quick Scoping Review (QSR) of the research into river asset condition and ecosystem service delivery to explore the current state of knowledge. The review team developed a PICO (Population, Intervention, Control, Outcome) model to transpose the concepts of the research enquiry into a search strategy for the evidence base and used a Delphi screening exercise to prioritise a subset of literature for the narrative findings. VOSviewer was used to analyse the high‐level linguistic themes from the full list of references. This co‐designed, collaborative and objective QSR approach allowed us to examine a large body of literature in a reproducible manner while minimising bias, demonstrating best practice for evidence review that should be continuously updated, generating a ‘living evidence’ knowledge asset. The results of the review demonstrate there is some knowledge of the mechanisms linking the condition of river assets to the delivery of ecosystem services for the majority of the broad range of ecosystem services analysed, with the exception of some of the cultural services, where comparatively fewer studies explore this link. However, a clear understanding of the quantitative evidence of the relationships between condition and ecosystem service delivery is missing for all of the ecosystem services. This gap stems from a lack of standardised methodologies used across the studies and a focus on a narrow range of definitions of condition. The gap needs to be addressed in future research on the topic, and a first step is to adopt more standardised indicators of river asset condition.
Keywords: condition; cultural services; ecosystem services; natural capital; provisioning services; Quick Scoping Review; regulating services; rivers; 41 Environmental Sciences; 4104 Environmental Management; 8.1 Organisation and delivery of services; Marine Biology & Hydrobiology; 3103 Ecology; 3707 Hydrology